THE ROLE OF OPINION LEADER IN COMMUNICATION PARTICIPATION IN THE GREEN TOURISM VILLAGE OF BILEBANTE – CENTRAL LOMBOK - Lalu Nurcholis Husnu; Bambang Dwi Prasetyo; Maulina Pia Wulandari (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2024)
This study analyzes the role of opinion leaders in the transformation of Bilibante Green Tourism Village in Central Lombok, examining participatory communication and the challenges faced. Using a qualitative approach through observation, interviews, and documentation, the findings indicate that the role of opinion leaders can be divided into three eras: pre-transformation, transformation, and post-transformation. Inclusive communication strategies and the use of communication technologies were effective in encouraging community participation. Challenges included differing opinions and resistance to authority. The study concludes that opinion leaders successfully activated community participation but require further improvement in communication and overall community engagement.